Vertical Profiles of Abundance and Potential Activity of Methane-Oxidizing Bacteria in Sediment of Lake Biwa, Japan - Tsutsumi, Masazumi (Japanese Society of Microbial Ecology/The Japanese Society of Soil Microbiology, 2012)
Vertical profiles of the abundance, community composition, and potential activity of methane-oxidizing bacteria (MOB) were investigated in the sediment of Lake Biwa. Sediment samples were obtained from two sites at different water depths. The abundance of MOB was assessed as the copy number of the pmoA gene (encoding the alpha subunit of particulate methane monooxygenase), measured with quantitative real-time PCR. Abundance of the pmoA gene peaked in the 5–8 cm layer of the sediment from both sites. MOB community composition was investigated by denaturing gradient gel electrophoresis (DGGE) analysis of pmoA and 16S rRNA genes. The band patterns observed in DGGE did not significantly differ with sediment depths or sampling sites. Sequence analysis of the DGGE bands indicated the dominance of the genus Methylobacter. Potential activity, which was measured in the presence of sufficient amounts of methane and oxygen, decreased linearly from the sediment surface to deeper layers. These results suggest that the pmoA gene copy number cannot be regarded as an indicator of aerobic MOB that retain potential activity in sediments.